Measuring the body of god: Temple plan construction and proportional measurement in early texts on north Indian architecture - Jaskūnas, Valdas (Acta Orientalia Vilnensia, 2008)
Vilnius University By reconsidering the fragments from early texts on north Indian temple architecture, namely the Purāṇas and their supposed sources, this paper sets out to explore the accounts of arrangement of the plans for temple ground plans and the modes of proportional measurement. It is contended that the general system of proportional measurement, called sāmānya or sarvasādhāraṇa and elaborated on in the texts under discussion, comprises temple garbha-shrines of various scales and forms, from which measurements for the entire temple structure are derived. The importance given to the garbha-shrine is attested by the method of classification of diverse temple types that are distinguished by the geometrical form of the ground plan of the garbha-shrine. It is consequently suggested that the arrangement of the ground plan of a garbha-shrine adapted by temple architects most probably reiterated the practices used for building Vedic altars, the layouts of which, as the Śulbasūtras state, might have served as models for structuring the ground plans of garbha-shrines.